Double toughening Ti-based bulk metallic glass composite with high toughness, strength and tensile ductility via phase engineering. (March 2021) - Lin, Shifeng; Ge, Shaofan; Zhu, Zhengwang; Li, Wei; Li, Zhengkun; Li, Hong; Fu, Huameng; Wang, Aimin; Zhuang, Yanxin; Zhang, Haifeng
Highlights: Phase engineering provides a novel route for developing high-performance bulk metallic glass composites. The prepared bulk metallic glass composite consists of β-phase, α-phase and glassy phase. The composite possesses the tensile yield strength of ~ 1410 MPa, ultimate tensile strength of ~ 1625 MPa, tensile ductility of ~ 3.6%, and fracture toughness of ~ 110MPa∙m 1/2 . The mechanical property of the composite is enhanced through the double toughening of α-phase and β-phase. Abstract: The popular strategy of overcoming the brittle fracture of bulk metallic glasses (BMGs) is to develop BMG composites (BMGCs). Most BMGCs consist of a single crystalline phase and glassy phase, and they display enhanced plasticities. However, these BMGCs usually display a trade-off in strength, ductility and fracture toughness as most engineering structural materials, which severely hampers their industrial application. To obtain a pronounced combination in tensile strength, tensile ductility and fracture toughness, the multiphase reinforced dispersive Ti-based BMG composite was successfully prepared via phase engineering. The as-prepared BMGC consists of β-phase, α-phase and glassy phase. The composite manifested the tensile mechanical properties with the yield strength of ~ 1410 MPa, ultimate tensile strength of ~ 1625 MPa, and tensile ductility of ~ 3.6%, and fracture toughness of ~ 110 MPa∙m 1/2 . The outstanding tensile properties are attributed to the double toughening of α-phase and β-phase. The high fracture toughness is ascribed to that the coarser dual crystalline phases lead to the devious crack propagation and crack bridging. Our work highlights a novel route for developing high-performance BMGCs. Graphical abstract: Image, graphical abstract